2016
DOI: 10.1016/j.paid.2015.11.043
|View full text |Cite
|
Sign up to set email alerts
|

The freedom to excel: Belief in free will predicts better academic performance

Abstract: Increasing evidence supports the importance of beliefs in predicting positive outcomes in life. This study examines the performance implications of the belief in free will as an abstract, philosophical belief that views the self as free from internal and external constraints and capable of choosing and directing one's own path. In Study 1 (N = 116, undergraduates), belief in free will was associated with higher performance on an academic proofreading task. In Study 2 (N = 614, undergraduates), we examined perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 56 publications
(66 reference statements)
1
54
0
2
Order By: Relevance
“…A growing body of evidence has shown that believing in free will is associated with a variety of positive life outcomes, including feeling grateful for past events (MacKenzie et al, 2014), better job performance (Stillman et al, 2010), higher academic achievement (Feldman et al, 2016), passionate love (Boudesseul et al, 2016), satisfaction with life (Li et al, 2017), and lower levels of perceived stress (Crescioni et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence has shown that believing in free will is associated with a variety of positive life outcomes, including feeling grateful for past events (MacKenzie et al, 2014), better job performance (Stillman et al, 2010), higher academic achievement (Feldman et al, 2016), passionate love (Boudesseul et al, 2016), satisfaction with life (Li et al, 2017), and lower levels of perceived stress (Crescioni et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In their work exploring lay understandings of free will, Monroe and Malle (2010, 2014) found that people’s definitions of what it means to have free will differed from philosophical understandings that typically view free will as the ability for our conscious minds (or a soul) to make decisions, regardless of brain states or prior causal events (Harris, 2012). Rather, people defined free will as their freedom to make choices and the ability to act without constraints—that is, their sense of personal control (see also Baumeister and Monroe, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Woodfield et al (2006) argue that the focus of attention has been on cognitive ability and personality variables, where the five-factor model dominated. More recently a belief in free will has been identified as correlating with better academic performance (Feldman et al, 2016). Identifying characteristic traits of the individual as an approach has many of the disadvantages of the demographic approach of Fowler and Norrie (2009).…”
Section: Introductionmentioning
confidence: 99%
“…As with the studies using other psychometric measures (e.g. Feldman et al, 2016) we cannot assume causation. Unpicking the relationship between this lack of confidence and relatively poor academic performance would be a useful qualitative study that might help us tailor interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Woodfield et al (2006) argue that the focus of attention has been on cognitive ability and personality variables, where the five-factor model has dominated. More recently a belief in free will has been identified as correlating with better academic performance (Feldman et al, 2016). A more specific measure relating to higher education is the Student Adaptation to College Questionnaire (Baker and Siryk, 1989) which has been shown to be an effective measure of adjustment to college (Credé and Niehorster, 2012) although its factor structure appears to vary with populations (Feldt et al 2011).…”
Section: Introductionmentioning
confidence: 99%